Familiar soil conditions help Pinus ponderosa seedlings cope with warming and drying climate. (15th March 2020) - Remke, Michael J.; Hoang, Tonny; Kolb, Thomas; Gehring, Catherine; Johnson, Nancy C.; Bowker, Matthew A.
Abstract : Changes in temperature and moisture as a result of climate forcing can impact performance of planted trees. Tree performance may also be sensitive to new soil conditions, for example, brought about by seeds germinating in soils different from those colonized by ancestral populations. Such "edaphic constraint" may occur with natural migration or human‐assisted movement. Pinus ponderosa seedlings, sourced from one location ("home" site), were grown across a field environmental gradient in either their original home soil or in soils from two different "away" sites. Seedlings were inoculated with site‐specific soil organisms by germinating seeds in living soil. After 6 months, the inoculated seedlings were transplanted into sterilized soils from the home or away sites. This experimental design allowed us to uncouple the importance of abiotic and biotic soil properties and test (1) how biotic and abiotic soil properties interact with climate to influence plant growth and stress tolerance, and (2) the role of soil biota in facilitating growth in novel environments. Seedlings grew least in hotter and drier away sites with away soil biota. Home soil biota ameliorated negative impacts on growth of hotter and drier away sites. Measurements of photosynthetic rate, stomatal conductance, and chlorophyll florescence (Fv/Fm) suggest that edaphic constraint reduced growth by increasing tree water stress. Results suggest that success of Ponderosa pine plantings into warming environments will be enhanced by pre‐inoculation with native soil biota of the seed source.